Enhancement of therapeutic efficacy of betanin for diabetes treatment by liposomal nanocarriers. (August 2019) - Amjadi, Sajed; Mesgari Abbasi, Mehran; Shokouhi, Behrooz; Ghorbani, Marjan; Hamishehkar, Hamed
Graphical abstract: Highlights: The betanin-loaded liposomes were fabricated and characterized. The liposomal encapsulation improved the in vitro digestion stability of betanin. Betanin-loaded liposomes positively regulate hyperglycemia and oxidative stress. Betanin-loaded liposomes showed high therapeutic potency for diabetes treatment. Abstract: Betanin is a bioactive compound with a high antioxidant activity and therapeutic potential. However, incomplete oral absorption and low stability of betanin limit its application. To surmount these limitations, betanin was encapsulated with nanoliposomes, nanoparticles exhibiting suitable physicochemical properties. Additionally, betanin-loaded nanoliposomes revealed a relatively good sustained release profile in the simulated gastric and intestinal fluids. In vitro digestion stability of betanin and its antioxidant activity were significantly improved by liposomal encapsulation. These nanocarriers were assessed in vivo for their therapeutic potency in streptozotocin induced rats. The results showed that the administration of betanin-loaded nanoliposomes was significantly more effective than free betanin in positively regulate hyperglycemia, hyperlipidemia and oxidative stress. Moreover, the histopathological analysis showed that the tissue damage in kidney, liver and pancreas was reduced in the betanin-loaded nanoliposomes treated diabetic rats. In conclusion nanoliposomes are suitable nanocarriers for improving the stability and therapeutic potential of betanin.